2019
DOI: 10.1016/j.apmr.2018.07.437
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes for Critically Ill Cardiovascular Patients Through Increased Physical Therapy Staffing

Abstract: Additional CVICU-dedicated PT staff was associated with increased PT treatment and reductions in CVICU and post-CVICU LOS. The effects of each were greatest for hospital survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Prior literature demonstrates that increasing rehabilitation staff can affect outcomes. 41 Patients in this study had a high severity of acute illness (median SOFA score of 13), high percentage of concomitant MV, high frequency of receiving blood products, and a high prevalence of liver disease and end-stage kidney disease. Of the 112 rehabilitation sessions, 72% were performed in patients with both CRRT and MV.…”
Section: Discussionmentioning
confidence: 83%
“…Prior literature demonstrates that increasing rehabilitation staff can affect outcomes. 41 Patients in this study had a high severity of acute illness (median SOFA score of 13), high percentage of concomitant MV, high frequency of receiving blood products, and a high prevalence of liver disease and end-stage kidney disease. Of the 112 rehabilitation sessions, 72% were performed in patients with both CRRT and MV.…”
Section: Discussionmentioning
confidence: 83%
“…Although data suggest that application of early mobilization is safe and feasible, its impact on mortality is not well defined. Limited studies have prospectively assessed the effect of early mobilization on patients receiving ECMO, but suggest a benefit [ 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, management of patients with refractory respiratory failure on ECMO without positive pressure ventilation is a promising and increasingly utilized therapeutic strategy. The rationale of endotracheal extubation is based on minimizing exposure to the known complications of positive-pressure ventilation [ 22 ] and supporting early mobilization [ 21 ]. In this study, we demonstrated that patients with ARDS removed from positive pressure ventilation had increased survival to hospital discharge, increased ventilator free days, and earlier mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al recently described a retrospective pre-/post-subgroup analysis in 114 acute critically ill cardiovascular patients with a mean daily treatment time at baseline of 51.7 min and a mean frequency of treatment in the ICU of 0.59 per day (36). Their analysis showed that an increased amount of therapies resulted in shorter length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…described highly active therapies, such as sit-to-stand transfers and marching on the spot (36), and used a clinical decision-making flowsheet for progression.…”
Section: Discussionmentioning
confidence: 99%